1999
DOI: 10.1021/jp990736m
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Effect on Hydrogen Atom Tunneling from Alkane to Free Deuterium Atoms in Cryogenic Solid

Abstract: ESR study on alkyl radicals generated in deuterated organic matrixes at 77 K by hydrogen atom tunneling from alkane molecules to free deuterium atoms has been carried out for elucidating control factors for the tunneling. For small alkane molecules, the tunneling rate is determined by the height of the potential energy barrier for the tunneling. For larger molecules in glassy matrixes, the rate decreases with increasing number and length of alkyl chains bonded to a carbon atom to be hydrogen abstracted. The tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Hydrogen-atom abstraction from alkanes results in the change of the bond orbitals of the reacting carbon from the initial sp 3 to the final sp 2 configuration, which accompanies the change of the C−C−C bond angle. As shown in the previous paper, the optimized geometrical structure of the reaction system at the exit of the tunneling channel is not far from the product state, so that the suppression of the angular change by matrix molecules causes the increase of the potential energy and thereby a decrease of the tunneling rate. The suppression is larger for longer alkyl chains, so that hydrogen atoms are preferentially abstracted from carbon atoms with shorter alkyl chains, even if the rate of hydrogen-atom abstraction by thermal activation is the same or slower.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Hydrogen-atom abstraction from alkanes results in the change of the bond orbitals of the reacting carbon from the initial sp 3 to the final sp 2 configuration, which accompanies the change of the C−C−C bond angle. As shown in the previous paper, the optimized geometrical structure of the reaction system at the exit of the tunneling channel is not far from the product state, so that the suppression of the angular change by matrix molecules causes the increase of the potential energy and thereby a decrease of the tunneling rate. The suppression is larger for longer alkyl chains, so that hydrogen atoms are preferentially abstracted from carbon atoms with shorter alkyl chains, even if the rate of hydrogen-atom abstraction by thermal activation is the same or slower.…”
Section: Resultsmentioning
confidence: 77%
“…Although we do not know the reason for the discrepancy, it may be worthwhile to point out that the spectral separation of the resultant CH 3 C*HCH 2 CH 2 CH 3 and CH 3 CH 2 C*HCH 2 CH 3 radicals is very difficult, since both of them give octet spectra with the separation of 2.2 mT. 7 Our result is in agreement with that by Kelley et al 8 On the basis of product analyses, they concluded that the tunneling rate of hydrogen atoms to the penultimate vinyl carbon of CH 3 CHd CHCH 2 CH 3 was the same as that to the antepenultimate one.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations